The involvement of trauma survivors in hospital-based injury prevention, violence intervention and peer support programs: A scoping review. Issue 8 (August 2022) - Zwaiman, Ashley; da Luz, Luis T.; Perrier, Laure; Hacker Teper, Matthew; Strauss, Rachel; Harth, Tamara; Haas, Barbara; Nathens, Avery B.; Gotlib Conn, Lesley
Highlights: Trauma survivors have been involved in trauma care programs for decades, but little is known about them and what their involvement looks like. A scoping review examined hospital-based injury prevention, violence intervention and peer support programs that involved trauma survivors. Thirty-six identified articles described who involved trauma survivors are and what they do with great variability across and within programs types. Outcomes related to trauma survivors' own experiences and the impacts to them of program involvement were under-studied. Significant opportunity exists to build our knowledge base of trauma survivors' roles and their impact in trauma care. Abstract: Background: Despite decades-long involvement of trauma survivors in hospital-based program delivery, their roles and impact on trauma care have not been previously described. We aimed to characterize the literature on trauma survivor involvement in hospital-based injury prevention, violence intervention and peer support programs to map what is currently known and identify future research opportunities. Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology. Articles were identified through electronic databases and gray literature. Included articles described hospital-based injury prevention programs, violence intervention programs and peer support programs that involved trauma survivors leveraging their injury experiences to counsel others. Studies were screened and data were abstracted in duplicate. Data were synthesized generally and by program type. Results: Thirty-six published articles and four program reports were included. Peer support programs were described in 21 articles, mainly involving trauma survivors as mentors or peer supporters. Peer support programs' most commonly reported outcome was participant satisfaction ( n  = 6), followed by participant self-efficacy ( n  = 5), depression ( n  = 4), and community integration ( n  = 3). Eleven injury prevention studies were included, all involving trauma survivors as speakers in youth targeted programs. Injury prevention studies commonly reported outcomes of participants' risk behaviors and awareness ( n  = 9). Violence intervention programs were included in four articles involving trauma survivors as intervention counsellors. Recidivism rate was the most commonly reported outcome ( n  = 3). Variability exists across and within program types when reporting on involved trauma survivors' gender, age, selection and training, duration of involvement and number of survivors involved. Outcomes related to trauma survivors' own experiences and the impacts to them of program involvement were under-studied. Conclusions: Significant opportunity exists to fill current knowledge gaps in trauma survivors' involvement in trauma program delivery. There is a need to describe more fully who involved trauma survivors are to inform the development of effective future interventions.